(untitled) (Vietnam Journal of Community Medicine, 2023)
Treatment of chronic periodontitis consists of two phases: disease treatment and maintenance treatment. In particular, depending on the severity of the disease, the treatment stage is divided into two subgroups: non-surgical treatment and surgical intervention. Objectives: To evaluate the results of non-surgical periodontitis treatment in patients with type 2 diabetes treated as outpatients at Tra Vinh Provincial General Hospital 2018 - 2019. Research object and method: Periodontitis patients come for examination and treatment at the Odonto-Stomatology clinic, Tra Vinh Province General Hospital. Type 2 diabetes patients have 6.5% ≤ HbA1c ≤ 8%, - Have CPI 2 and CPI 3. Study design Cross-sectional description of the interventional study Result: After treatment, the GI index of gingivitis had 62.4% of patients with normal gums, 17.3% of patients with mild gingivitis, 8.4% with moderate gingivitis, and 11.9% with severe gingivitis. Plaque index has 59.7% of patients without plaque, 37.6% of patients with plaque covering < 1/3 of the tooth surface or with adhesions, 2.7% of patients with 1/3 < plaque < 2/3 of the tooth surface, no case has plaque covering > 2/3 of the tooth surface. CAL adhesion index was improved after the intervention: the adhesion loss index 0 was 100%, and the level 1 adhesion loss index decreased to 0%. The state of bone resorption on radiographs: Good (28.8%), Moderate (bone loss ≥ 20%) is 47.9%, Good (Bone loss < 20%) is 23.3%. Conclude: After 3 months of treatment, all indexes of GI, PLI, CPITN, CAL improved markedly.